Internal iliac artery thrombosis in a 2-month-old infant with incomplete Kawasaki disease - Musa, Husna; Yubbu, Putri; Koh, Ghee Tiong (Cambridge University Press (CUP), 2019)
We report a case of a 2-month-old infant with incomplete Kawasaki disease with multiple coronary and systemic arteries aneurysms complicated with internal iliac arteries thrombosis. The atypical clinical presentations and severity of systemic vascular involvements discuss the importance of high index of suspicions in younger infants and treatment options in such cases.